ch2extra - Using the definition f ( x + h ) = -2( x + h ) +...

Info iconThis preview shows pages 1–6. Sign up to view the full content.

View Full Document Right Arrow Icon
Definition of the Derivative Using Average Rate (Page 129 - 133 and 160 in the book) a a+h f(a) Slope of the line = h f(a+h ) Average Rate of Change = f ( a+h ) – f ( a ) h f ( a+h ) – f ( a ) h
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
a+h h a a+h h a a h Now, Watch what happens when: Point a is fixed and the size of the interval h shrinks a+h h a
Background image of page 2
As h shrinks and approaches zero (but not = 0), Slope of the Tangent line = f ( a+h ) – f ( a ) h h f(a+h ) f(a) a+h a Slope of the line = Average Rate of Change = f ( a+h ) – f ( a ) h the line becomes a Tangent Line As h approaches zero
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
f(a) a lim: Limit, as h approaches zero f ( a+h ) – f ( a ) h = lim h 0 Slope of the Tangent line As h approaches zero, or: f ( a+h ) – f ( a ) h = The slope of the Tangent Line at a is the Derivative, f ' ( a ) f ( a+h ) – f ( a ) h lim h 0 f ' ( a ) =
Background image of page 4
Example: Use the definition of the derivative to obtain the following result: If f ( x ) = -2 x + 3, then f ' ( x ) = -2 Solution:
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 6
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Using the definition f ( x + h ) = -2( x + h ) + 3 = (-2 x- 2 h + 3 ) = -2 f ( x+h ) f ( x ) h f ' ( x ) = lim h = (-2 h ) h lim h = (-2 x- 2 h + 3 ) (-2 x + 3) h lim h f ( x + h ) f ( x ) h f ' ( x ) = lim h Example: Use the definition of the derivative to obtain the following result: If f ( x ) = x 2- 8 x + 9, then f ' ( x ) = 2 x- 8 f ( x + h ) = ( x + h ) 2- 8( x + h ) + 9 = ( x 2 + 2 xh + h 2- 8 x-8 h + 9 ) = 2 x - 8 f ( x+h ) f ( x ) h f ' ( x ) = lim h = (2 x + h- 8) lim h = h (2 x + h- 8) h lim h = (2 xh + h 2- 8 h ) h lim h = ( x 2 + 2 xh + h 2- 8 x- 8 h + 9 ) ( x 2- 8 x + 9) h lim h f ( x + h ) f ( x ) h f ' ( x ) = lim h Solution: Using the definition...
View Full Document

This note was uploaded on 02/29/2012 for the course MATH 119 taught by Professor Maanomran during the Fall '09 term at Indiana University-Purdue University Fort Wayne.

Page1 / 6

ch2extra - Using the definition f ( x + h ) = -2( x + h ) +...

This preview shows document pages 1 - 6. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online